Interruptions during pediatric medication preparation and administration - Özkan, Suzan; Kocaman, Gülseren; Öztürk, Candan (GALENOS YAYINCILIK, 2016)
Aim: Any interruption or distraction during the process of medication administration might cause a medication error. Materials and Methods: This observational study examined frequency and reasons of interruptions during preparation and administration of pediatric medications. Two thousand three hundred forty four medication doses were observed during 200 medication administration round. Data regarding the interruptions that occur during the preparation and administration of medications were collected for one calendar year. Frequencies and percentage distributions were calculated for the interruptions as well as their reasons. Results: An interruption of 36.1% occurred during this process. Most frequent interruption reasons are mothers, physicians and nurses. Sixty-one errors were made on total of interruptions. Conclusion: Findings in this study present importance of establishment of clinical and institutional environment for nurses to safe medication administration, in terms of patient safety.

Amaç: İlaç uygulama sürecindeki herhangi bir bölünme ya da dikkat dağınıklığı ilaç hatasına neden olabilmektedir. Gereç ve Yöntemler: Bu araştırmada, hemşirelerin ilaç hazırlama ve uygulama sırasında yaşadıkları bölünmelerin sıklığı ve nedenlerinin belirlenmesinde gözlem yöntemi kullanılmıştır. İki yüz ilaç uygulama saatinde 2,344 ilaç uygulama süreci gözlemlenmiştir. İlaç hazırlama ve uygulama sırasında yaşanan bölünmelere ilişkin veriler bir takvim yılında toplanmıştır. Bölünmelerin sıklık ve yüzde dağlımı yapılmıştır. Bulgular: İlaç uygulama sürecinde %36,1 oranında bölünme olmuştur. En sık bölünme nedenleri anneler, hekimler ve hemşirelerdir. Bölünmeler nedeni ile 61 hata yapılmıştır. Sonuç: Bu çalışmanın sonuçları, hemşirenin güvenli ilaç hazırlama ve uygulamasına yönelik klinik ve kurumsal ortamın oluşturulmasının hasta güvenliği açısından önemini ortaya koymaktadır.
WOS: 000406928300008
Keywords: Human error; interruption; medication safety; nurses; pediatric; İnsan hatası; Bölünme; İlaç güvenliği; Hemşire; Pediatri